Human Development IX: A Model of the Wholeness of Man, His Consciousness, and Collective Consciousness - Søren Ventegodt; Tyge Dahl Hermansen; Trine Flensborg-Madsen; Erik Rald; Maj Lyck Nielsen; Joav Merrick (The Scientific World Journal)
In this paper we look at the rational and the emotional interpretation of reality in the human brain and being, and discuss the representation of the brain-mind (ego), the body-mind (Id), and the outer world in the human wholeness (the I or “soul”). Based on this we discuss a number of factors including the coherence between perception, attention and consciousness, and the relation between thought, fantasies, visions and dreams. We discuss and explain concepts as intent, will, morals and ethics. The Jungian concept of the human collective conscious and unconscious is also analyzed. We also hypothesis on the nature of intuition and consider the source of religious experience of man. These phenomena are explained based on the concept of deep quantum chemistry and infinite dancing fractal spirals making up the energetic backbone of the world. In this paper we consider man as a real wholeness and debate the concepts of subjectivity, consciousness and intent that can be deduced from such a perspective.